Wireless sensor networks for civil infrastructure monitoring a best practice guide - Rodenas-Herráis, David; Soga, Kenichi; Fidler, Paul R. A; De Battista, Nicholas (Cambridge Centre for Smart Infrastructure and Construction, 2016)
This guide is intended to offer best practice guidance compiled from recent research and development from both industry and academia on the monitoring of civil engineering infrastructure with wireless sensor network technology. It is designed to provide a well-defined strategy for the implementation of WSNs in infrastructure and to make the decision-making process more effective by offering advice on good practice for data interpretation and information valuation for a variety of asset types. It will also offer advice on what to do with the data obtained, and then how to proceed upon the project completion, i.e. when the monitoring tasks are finished.